2014
DOI: 10.1007/s00192-014-2418-6
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum urinary retention: a systematic review of adverse effects and management

Abstract: Based on current literature, evidence stating that PUR is harmless is lacking. Future research should focus on management strategies for overt PUR and the long-term consequences of covert PUR. Until these results are available, clinicians should be aware of the potential consequences and therefore keep trying to identify patients at risk of PUR and patients with the actual condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 54 publications
2
87
1
6
Order By: Relevance
“…Although ultrasonographic measurement of PVRBV in the postpartum patient is doubtful, due to postpartum uterine size (7), several authors (23,24) offer assessment of the bladder accurately by ultrasound, even in the postpartum period. In a recent review including 24 studies, it was concluded that a standard treatment guideline for PPUR is necessary, since there is no sufficient evidence about the catheterization methods for overt PPUR (25). In the same review, it was recommended that both overt and covert PPUR should be regarded as serious conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasonographic measurement of PVRBV in the postpartum patient is doubtful, due to postpartum uterine size (7), several authors (23,24) offer assessment of the bladder accurately by ultrasound, even in the postpartum period. In a recent review including 24 studies, it was concluded that a standard treatment guideline for PPUR is necessary, since there is no sufficient evidence about the catheterization methods for overt PPUR (25). In the same review, it was recommended that both overt and covert PPUR should be regarded as serious conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in the adrenergic and cholinergic innervation of the bladder has been observed after induced urinary retention and bladder overdistension in rats (31,59). Whether women suffer neuroanatomic changes in the bladder with labor is unknown, although it is possible, since urinary retention is a well-known condition after childbirth, with epidural analgesia, prolonged labor, episiotomy, and high birth weight as risk factors (28,37,38). The epidural analgesia commonly used to avoid pain during labor causes bladder hypotonia and eliminates the normal sensation to void, leading to bladder overdistension (62), which may damage the detrusor and consequently induce long-term voiding difficulties (64).…”
Section: 56)mentioning
confidence: 99%
“…Postpartum urinary retention (PUR), or voiding dysfunction, is a well-known phenomenon in the puerperium (Yip et al, 2004;Mulder et al, 2014). The incidence of PUR varies from 0.5 to 45% in women who have just delivered babies.…”
Section: Introductionmentioning
confidence: 99%
“…The pelvic floor muscles and pudendus nerve may be damaged during labour, resulting in reduced bladder sensitivity (Saint et al, 2009). Peri-urethral and valvular oedema may cause obstruction (Mulder et al, 2014). Finally, reduced pressure from the uterus after birth may lead to incomplete bladder emptying during the first hours to days after delivery (Saultz et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation